PENGARUH MOTIVASI DAN PEMBERDAYAAN KARYAWAN TERHADAP KINERJA KARYAWAN PT. HD MOTOR 99 DENPASAR - Putri, Adetya Vianty; Ardana, I Komang (E-Jurnal Manajemen; Vol 5 No 11 (2016), 2016)
This research is motivated by concerns regarding the performance of employees at PT. HD Motor 99 Denpasar not optimal caused by motivation and employee empowerment. The purpose of this research is to analyze the influence of motivation and employee empowerment on employee performance. This research was conducted at PT. HD Motor 99 Denpasar. The samples used as many as 57 employees, using sampling methods saturated. Data collected through observation, interviews and questionnaires. Technical analysis of the data used is multiple linear regression analysis. Based on the analysis of data, the motivation is significantly positive effect on employee performance. Employee empowerment is significantly positive effect on employee performance. To improve the performance of employees, companies should give awards to improve employee performance. In addition, the company is expected to provide greater opportunities for employees on job involvement.
Keywords: : motivation, employee empowerment, performance